Tra insegnamento e ricerca. Entre enseignement et recherche: La storia della Rivoluzione francese. L'histoire de la Révolution française Between Teaching and Research: The History of the French Revolution - Anna Maria Rao (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2015)
What is the place of the French Revolution in teaching history? What are the ideological trends and pedagogic messages that are used in school textbooks? Are these textbooks simple "national autobiographies" or the faithful reflection of historical research on the topic? The contributions collected in this volume seek to answer some of these questions, taking into account different countries, from France to Russia, from the United States to China. In a time like ours, where much is said about the public use of history, the relationship between historical research, teaching and dissemination remains a fundamental theme.